PTP1B Inhibition Causes Rac1 Activation by Enhancing Receptor Tyrosine Kinase Signaling - Ayako Tsuchiya; Takeshi Kanno; Hisao Nagaya; Tadashi Shimizu; Akito Tanaka; Tomoyuki Nishizaki (Cellular Physiology and Biochemistry, 2014)
Background/Aims: The present study investigated the signaling pathway underlying Rac1 activation induced by the linoleic acid derivative 8-[2-(2-pentyl-cyclopropylmethyl)-cyclopropyl]-octanoic acid (DCP-LA). Methods: Activity of protein tyrosine phosphatase 1B (PTP1B) was assayed under cell-free conditions. Western blot was carried out to quantify phosphorylation of insulin receptor substrate-1 (IRS-1) and Akt in PC-12 cells. Rac1 activity was monitored in the föerster resonance energy transfer (FRET) analysis using living and fixed PC-12 cells. Results: DCP-LA markedly suppressed PTP1B activity in a concentration (100 pM-100 µM)-dependent manner. In the DCP-LA binding assay, fluorescein-conjugated DCP-LA produced a single fluorescent signal band at 60 kDa, corresponding to the molecule of PTP1B, and the signal was attenuated or abolished by co-treatment or pretreatment with non-conjugated DCP-LA. DCP-LA significantly enhanced nerve growth factor (NGF)-stimulated phosphorylation of IRS-1 at Tyr1222 and Akt1/2 at Thr308/309 and Ser473/474 in PC-12 cells. In the FRET analysis, DCP-LA significantly enhanced NGF-stimulated Rac1 activation, which is abrogated by the phosphatidylinositol 3 kinase (PI3K) inhibitor wortmannin, the 3-phosphoinositide-dependent protein kinase-1 (PDK1) inhibitor BX912, or the Akt inhibitor MK2206. Conclusion: The results of the present study show that DCP-LA-induced PTP1B inhibition, possibly through its direct binding, causes Rac1 activation by enhancing a pathway along a receptor tyrosine kinase (RTK)/IRS-1/PI3K/Akt/Rac1 axis.